Multiply lensed star forming clumps in the A521-sys1 galaxy at redshift 1. Issue 2 (4th August 2022) - Messa, Matteo; Dessauges-Zavadsky, Miroslava; Richard, Johan; Adamo, Angela; Nagy, David; Combes, Françoise; Mayer, Lucio; Ebeling, Harald
ABSTRACT: We study the population of star-forming clumps in A521-sys1, a $z=1.04$ system gravitationally lensed by the foreground ($z=0.25$ ) cluster Abell 0521. The galaxy presents one complete counter-image with a mean magnification of $\rm μ \sim 4$ and a wide arc containing two partial images of A521-sys1 with magnifications reaching $μ > 20$, allowing the investigations of clumps down to scales of ${\rm R}_{\rm eff} < 50$ pc. We identify 18 unique clumps with a total of 45 multiple images. Intrinsic sizes and UV magnitudes reveal clumps with elevated surface brightnesses comparable to similar systems at redshifts $z\gtrsim 1.0$ . Such clumps account for ${\sim}40\, \rm{per\ cent}$ of the galaxy UV luminosity implying a significant fraction of the recent star-formation activity is taking place there. Clump masses range from 10 6 to $10^9\, {\rm M}_\odot$ and sizes from tens to hundreds of parsec resulting in mass surface densities from 10 to $10^3\, {\rm M}_\odot\, {\rm pc}^{-2}$ with a median of ${\sim}10^2\, {\rm M}_\odot\, {\rm pc}^{-2}$ . These properties suggest that we detect star formation taking place across a wide range of scale from cluster aggregates to giant star-forming complexes. We find ages of less than 100 Myr consistent with clumps being observed close to their natal region. The lack of galactocentric trends with mass, mass density, or age and the lack of old migrated clumps can be explained either by dissolution of clumps after few ∼100 Myr or by stellar evolution making them fall below the detectability limits of our data.